1998
DOI: 10.1111/j.1540-8159.1998.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous Dysfunction and the Change of Blood Viscosity During Head‐Up Tilt

Abstract: The precise stimulus that induces vasovagal syncope is still unclear. We have previously demonstrated that the peripheral distribution of blood volume (venous pooling) is a strong predictor of tilt induced vasovagal reaction. We hypothesized that an increase in venous pooling during tilt accentuates the measured increase in blood viscosity. This hypothesis is based on the previously demonstrated increase in venous pressure and subsequent increase in transcapillary fluid transudation during tilt. The increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…41,42 Contributions may also arise from changes in hematocrit and in blood viscosity. 43 Of these variants the redistributive form is most common. This has been attributed to lower extremity blood pooling and vasodilation in “neurogenic POTS,” 44,45 or to our category of “normal flow POTS” in which splanchnic vasodilation and blood pooling occur.…”
Section: Why Are “Positive” Tilt Test Results Similar (Early On) In Fmentioning
confidence: 99%
“…41,42 Contributions may also arise from changes in hematocrit and in blood viscosity. 43 Of these variants the redistributive form is most common. This has been attributed to lower extremity blood pooling and vasodilation in “neurogenic POTS,” 44,45 or to our category of “normal flow POTS” in which splanchnic vasodilation and blood pooling occur.…”
Section: Why Are “Positive” Tilt Test Results Similar (Early On) In Fmentioning
confidence: 99%
“…The decrease in venous return to the heart by an exaggerated shift in blood volume from central to peripheral vascular bed has been suspected as a precipitating factor for the development of syncope [3,4]. A trend for greater peripheral blood pooling and a reduced venous volume variability was reported in patients with neurally mediated syncope [5], whereas another study failed to clearly demonstrate the relationships between venous pooling, blood viscosity and head-up tilt (HUT) [6]. Other studies have suggested impaired change in peripheral venous tone [5,7], although no differences in venous compliance between controls and patients with postural tachycardia syndrome have been reported [8].…”
Section: Introductionmentioning
confidence: 98%
“…Interpretation and the predictive value of these findings remains limited by the small number of subjects studied with various etiologies for syncope (e.g. orthostatic intolerance [6] and postural tachycardia [8]), leaving the contribution of both exaggerated venous pooling and impaired circulatory adjustment to be clarified in the routine diagnostic framework of syncope of unexplained origin. In our present study, the heterogeneity of etiologies for syncope was reduced by the exclusion of patients with postural tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…This blood redistribution results in a decrease in blood return to the heart, subsequently causing a decrease in stroke volume, cardiac output, and ultimately blood pressure (Yamanouchi et al. ; Dorey et al. ).…”
Section: Introductionmentioning
confidence: 99%